AGE-RELATED DISABILITY IN BATHING: A REVIEW OF THE RESEARCH LITERATURE - Salgamcıoglu, Berrak Karaca (European Scientific Journal, ESJ, 2013)
Disability in bathing is an important problem for older adults, affecting their daily lives and turning a pleasurable activity into a challenging task. In respond to it, modifications are being made either in bathing task or in bathing environment. The purpose of this review of the research literature is to answer some key questions about the nature of the modifications made in respond to disability in bathing and the efficacy of these modifications, to inform the new product design processes, and to set an agenda for future research. This article presents a review of literature on age-related disability in bathing and the modifications mentioned in published literature related to disability in bathing in older adults either by changing the environment to improve the ability of older adults to perform specific subtasks or by altering the bathing task, or both. Across sources, modifications that are made in respond to disability in bathing in older adults were listed and broad list of arguments both for and against these modifications were identified. Based on the review, it is being argued that environments need to be designed to prevent from disability, not modified in respond to it. Moreover, preferences of older adults needed to be taken to account more when designing aids and products for the bathroom. Disability in bathing needs to be researched with a focus on culture and religion, since they are important variables affecting older adults’ decisions.